Pengaruh Product Placement, Sponsor Event Fit, Dan Brand Exposure Terhadap Brand Awareness - Arthana, Gilang Hans; Isharina, Ikhtiara Kaideni (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2024)
The rapid development of the food and beverage industry has increasingly business competition. The increasing number of products with various brands appearing on the market require companies to recognize factors affecting brand awareness in order to win the competition. The purpose of this research is to examine the effect of product placement, sponsor event fit, and brand exposure toward the brand awareness Teh Kotak (study on Indonesian Idol XII audience in East Java.) This study adopts an explanatory research design with a quantitative approach. The sample size used was 160 respondents. Sampling used purposive sampling technique with the characteristics of a minimum age of 17 years, domiciled in East Java, and had watched advertising Teh Kotak on Indonesian Idol XII TV shows. The data analysis technique employed in this study was multiple linear regression and processed using the IBM SPSS program version 25. This study finds that product placement positively and significantly influences brand awareness, sponsor event fit positively and significantly influences brand awareness, and brand exposure positively and significantly influences brand awareness.   Abstrak Pesatnya perkembangan industri makanan dan minuman menyebabkan persaingan bisnis semakin ketat. Semakin bertambahnya jumlah produk dengan berbagai merek yang muncul di pasar membuat perusahaan perlu untuk mempertimbangkan faktor faktor yang dapat mempengaruhi brand awareness untuk memenangkan persaingan. Penelitian ini bertujuan untuk mengetahui pengaruh product placement, sponsor event fit dan brand exposure terhadap brand awareness Teh Kotak (studi pada penonton Indonesian Idol XII di Jawa Timur). Jenis penelitian ini adalah explanatory research dengan metode kuantitatif. Ukuran sampel yang digunakan sebanyak 160 responden, Pengambilan sampel menggunakan teknik purposive sampling dengan kriteria responden berusia minimal 17 tahun, berdomisili di Jawa Timur, dan pernah melihat iklan Teh Kotak dalam tayangan Indonesian Idol XII. Teknik analisis data menggunakan analisis regresi linier berganda dan diolah menggunakan bantuan program IBM SPSS versi 25. Hasil Penelitian ini menunjukkan bahwa (1) product placement berpengaruh positif dan signifikan terhadap brand awareness, (2) sponsor event fit berpengaruh positif dan signifikan terhadap brand awareness, dan (3) brand exposure berpengaruh positif dan signifikan terhadap brand awareness.